The long-term trend of uterine fibroid burden in China from 1990 to 2019: A Joinpoint and Age–Period–Cohort study - Liu, Xingyu; Wang, Bo; Zhang, Qianyu; Zhang, Jinjin; Wang, Shixuan (Frontiers in Physiology, 2023)
Purpose: Uterine fibroids occur in 40% to 60% of women and are symptomatic in 30% of patients by causing abnormal uterine bleeding, pelvic pressure, pain, and infertility, etc. The study aims to evaluate the long-term trend of uterine fibroids mortality and disability-adjusted life years (DALY) in China and the relative risks of age, period, and birth cohort effects. Methods: The mortality and disability-adjusted life years (DALY) of uterine fibroids from 1990 to 2019 were derived from the global burden of disease 2019. The annual percentage change and average annual percent change (AAPC) were assessed with joinpoint regression. The effects of age, period, and birth cohort on death and DALYs were analyzed by an age–period–cohort framework. Results: The age-standardized rates were all on the ascending trend, with the greatest rise in age-standardized mortality rate (AAPC, 1.53, 95%CI, 1.04, 2.02). The net drift was found to be 3.51% (95% CI, 2.25% to 4.78%) per year for mortality and 0.34% (95% CI, 0.14% to 0.53%) per year for DALY. Significant age, period, and birth cohort effects were found for mortality and DALY (for all, P < 0.001). The mortality risk increased overall with age, but the DALY risk increased first and then decreased with age. The period risk and birth cohort risk for mortality and DALY showed different trends. Conclusion: These secular time trends and changes of mortality and DALY reveal the socioeconomic alterations, reform of diagnosis and therapy, and changes in social lifestyles and behaviors. Uterine fibroids are still the most common benign gynecologic tumors in women, and more epidemiological investigations and social health prevention and control should be applied.